Keakuratan ChatGPT dalam Konsep Maf’ul Bih Berdasarkan Perspektif Musthafa al-Ghalayini dalam kitab Jāmi’ ad-Durūs al-‘Arabiyyah - Sanaya, Dini; Sulaikho, Siti (Borneo Journal of Language and Education, 2025)
The utilization of Artificial Intelligence has become an increasingly popular phenomenon among educators and learners including in Arabic language learning. Considering the wide accessibility and time efficiency, many individuals prefer to use AI as a learning resource without paying attention to the quality and validity of the data obtained. Based on this situation, this study aims to examine the accuracy of Arabic syntax rules (nahwu), especially in the maf'ūl bih chapter sourced from ChatGPT and compare it with the book Jāmi' ad-Durūs al-'Arabiyyah by Musthafā al-Galāyainī. This research uses a descriptive qualitative approach. The data collection method is done through literature study based on Klaus Kripendorff's content analysis technique. The analysis shows that ChatGPT is not only able to provide material about maf'ūl bih theoretically, but also includes interpretations in the form of perfect sentences. However, the AI chatbot has limitations in terms of the completeness and accuracy of the data presented. in general, the information sourced from ChatGPT is less detailed. In addition, the validity of the data generated is only found in the basic theory, namely in the sub-chapter on the definition of maf'ūl bih. Meanwhile, in a more in-depth discussion, namely the division and law of maf'ūl bih, the explanation presented by ChatGPT is not entirely accurate. This research is expected to contribute in opening a broader perspective on the importance of critical evaluation of the information generated by CHatGPT in nahwu learning, especially in the chapter of maf'ūl bih and provide new insights into the potential and limitations of AI technology in the context of Arabic l anguage education.